Investigating context-specific sedentary behaviours and cardiometabolic health in college-based young adults (CONTEXT-SB): a protocol for a longitudinal observational study - Justin B Moore; Lee Stoner; Craig Paterson; Feng-Chang Lin; Emma Cowley; Michelle L Meyer; Jake Christopher Diana; Aiden James Chauntry; Jeb F Struder; Patricia Pagan-Lassalle; Erik D Hanson (BMJ Open)
Background Sedentary behaviour (SB) is detrimental to cardiometabolic disease (CMD) risk, which can begin in young adulthood. To devise effective SB-CMD interventions in young adults, it is important to understand which context-specific SB (CS-SB) are most detrimental for CMD risk, the lifestyle behaviours that cluster with CS-SBs and the socioecological predictors of CS-SB.Methods and analysis This longitudinal observational study will recruit 500 college-aged (18–24 years) individuals. Two laboratory visits will occur, spaced 12 months apart, where a novel composite CMD risk score (eg, arterial stiffness, metabolic and inflammatory biomarkers, heart rate variability and body fat distribution) will be calculated, and questionnaires to measure lifestyle behaviours and levels of the socioecological model will be administered. After each laboratory visit, total SB (activPAL) and CS-SB (television, transportation, academic/occupational, leisure computer, ‘other’; ecological momentary assessment) will be measured across 7 days.Ethics and dissemination This study has received full ethical approval, and participants provide written informed consent. Our hypothesis is that certain CS-SB will show stronger associations with CMD risk, compared with total sedentary behaviour (T-SB), even after accounting for coexisting lifestyle behaviours. We also expect a range of intra-individual, inter-individual and physical environmental socioecological factors will predict CS-SB. Findings addressing both the primary and any secondary research aims will be submitted for publication in a high-impact peer-reviewed journal.